Avoiding the “Great Filter”: An assessment of climate change solutions and combinations for effective implementation - Zhang, Junze; Zhang, Kerry K.; Zhang, Mary; Jiang, Jonathan H.; Rosen, Philip E.; Fahy, Kristen A. (Frontiers in Climate, 2022)
Global climate temperatures have unmistakably risen, and naturally occurring climate variability alone cannot account for this trend. Human activities are estimated to have caused about 1°C of global warming above the preindustrial baseline, and if left unchecked, it will continue to drastically damage the Earth and its inhabitants. Attempts toward alleviating the effects of global warming have often been at odds and remain divided among a multitude of strategies, reducing the overall effectiveness of these efforts. It is evident that collaborative action is required for avoiding the most severe consequences of climate change. This article evaluates the main strategies (industrial/energy, political, economic, agricultural, atmospheric, geological, coastal, and social) toward both mitigating and adapting to climate change. Also, it provides an optimal combination of seven solutions that can be implemented simultaneously, working in tandem to limit and otherwise accommodate the harmful effects of climate change. Previous legislation and deployment techniques are also discussed as guides for future endeavors.